Effect of speed, agility, and quickness training on linear sprint, jump, and change of direction speed performance in soccer players: A systematic review and three-level meta-analysis - Uysal, H. S.; Korkmaz, S.; Sen, S.; Thapa, R. K.; Pojskic, H. (Strength and Conditioning Journal, 2024)
This systematic review and meta-analysis aimed to assess the effects of the speed, agility, and quickness (SAQ) training method on linear sprinting, jumping, and change of direction speed (CODS) performance in soccer players. Three electronic databases (Web of Science, PubMed, and Scopus) were searched, and 17 studies were included in the three-level meta-analysis. The results indicated that SAQ training significantly improved linear sprinting (effect size [ES] = 0.79, 95% CI = 0.19-1.39, p = 0.01, I2 = 95.9%), jumping (ES = 0.83, 95% CI = 0.26-1.39, p = 0.01, I2 = 85.9%), and CODS performance (ES = 0.70, 95% CI = 0.29-1.11, p = 0.01, I2 = 82.8%) when compared with the control groups. Furthermore, a moderating effect of sprint distance (favoring 10 m versus 20 or 30 m) was observed for the sprint performance. In addition, the moderating effect of jump type (favoring horizontal versus vertical) and training frequency (favoring >2 versus =2 sessions/week) was observed for jump performance. Finally, a moderating effect of age (favoring >15 versus =15 years) was observed for CODS. In conclusion, coaches may prefer SAQ training to improve sprint, jump, and CODS abilities of soccer players.